UJI AKTIVITAS ANTIOKSIDAN EKSTRAK AIR TANAMAN SEMANGGI (Marsilea crenata C.Presl) METODE FRAP (Ferric Reducing Antioxidant Power) - raisya adila adila; I.A.K. Pramushinta; A.S. Sinulingga (LPPM Universitas Abdurrab, 2024)
The clover plant (Marsilea crenata C.Presl) is a plant that is widely used for food and has the potential to be developed as a herbal medicine. Clover plant extract using methanol, chloroform, and ethyl acetate was found to have weak antioxidant activity. The aim of this research was to test the antioxidant activity in air solvent extracts of clover plants using the FRAP (Ferric Reducing Antioxidant Power) method and analyze the effect of variations in extract concentration on the antioxidant activity test. The method in this research is clover plant extraction by maceration using an air solvent. Test antioxidant activity using the FRAP method using a UV-Vis spectrophotometer with a maximum wavelength of 596 nm. The extract yield of 42% showed that it positively contained flavonoids, saponins, polyphenols and a water content of 9.94% Â± 0.1276. The results showed that clover plants had weak antioxidant activity (IC50 351.04 ppm) compared to vitamin C as a positive control which showed very strong antioxidant activity (IC50 22.60 ppm). From the results of this study, it can be said that increasing the extract concentration can increase the percentage of inhibition of free radical formation, but the increase is not linear, as indicated by the R2 value not approaching 0.99.